A facile spectroscopic method for measuring lignin content in lignocellulosic biomass. Issue 14 (25th June 2021) - Lu, Fachuang; Wang, Chen; Chen, Mingjie; Yue, Fengxia; Ralph, John
Abstract : A spectroscopic method was developed for the determination of lignin contents in lignocellulosic biomass, based on a full dissolution of the biomass sample in a cysteine–sulfuric acid solution at room temperature. Abstract : Although measuring lignin contents is a routine operation for biomass compositional analysis in process development aiming at efficient utilization of woody biomass, it is still a challenging task requiring many steps, hazardous reagents, heating, and a significant time. A facile spectroscopic method, our CASA (Cysteine–Assisted Sulfuric Acid) method, was developed to quantify the lignin content of lignocellulosic biomass, based on an extraordinary system in which biomass samples are fully dissolved in 72% H2 SO4 containing cysteine at 24 °C in 60 min. Using synthetic lignins, the lignin absorptivities were determined to be 17.25 g −1 L cm −1 for softwood lignin and 11.23 g −1 L cm −1 for hardwood lignin and monocot lignin. Seven softwoods, six hardwoods, and six monocots were tested using the CASA method. A high coefficient of determination ( R 2 = 0.95) was found between the CASA results and the acid-insoluble lignin contents, and an even better R 2 (0.98) was obtained when the CASA data were correlated with the total lignin contents.